Diskriminasi Upah Terhadap Perempuan yang Bekerja: A Perspective of Gender Work Place - Putri Rahmah Nurhakim; Ita Rodiah; Henky Fernando (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2023)
Gender discrimination in the workplace and inequality in pay have become widely debated topics. This article presents in-depth and concrete case studies to understand better how gender inequality affects individuals and organizations in the workplace. Case studies can cover the experiences of individuals who have faced pay discrimination, difficulties in achieving promotions, or other negative impacts arising from gender inequality. In addition, discrimination is also displayed in memes that reflect unfair salary differences between men and women who have the same qualifications, highlighting discrimination in promotions, gender stereotypes, and the wider economic gap that affects women in the workplace... The method used in writing this article is a literature review, virtual ethnography. The author tries to explain the issue of gender discrimination against wages through competent references to articles and books based on this study. The results of the research show that through memes and interviews, issues of gender discrimination in the workplace, especially in the context of wages, become more visible and make people aware of the inequalities that need to be addressed immediately.